1975
DOI: 10.2307/2495950
|View full text |Cite
|
Sign up to set email alerts
|

Russian Music and its Sources In Chant And Folk-Song. By Alfred J. Swan, New York: W. W. Norton, 1973. 234 pp. $12.50.

Abstract: art world during the twenties, which manages to be fascinating even when it involves only the dry recital of facts about the organization and encouragement of the arts under Lunacharsky's regime. Even though, as the author points out, the Soviet sources for such a study are incomplete and at times misleading, Drengenberg still has much to tell us about such matters as art education, art research, the protection and restoration of art monuments, as well as a kind of "socialist realism before the fact"-^the enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Modified David’s scores derive a dominance index from count data for each individual so that those typically “dominating” have a large positive score, and those that are typically “dominated” have large negative scores [ 46 ]. Brown’s ranking method minimizes the proportion of dyadic interactions where any lower ranking individual “wins” an interaction [ 48 ]. de Vries’ I & SI method minimizes the sum of rank differences between inconsistently ranked individuals [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified David’s scores derive a dominance index from count data for each individual so that those typically “dominating” have a large positive score, and those that are typically “dominated” have large negative scores [ 46 ]. Brown’s ranking method minimizes the proportion of dyadic interactions where any lower ranking individual “wins” an interaction [ 48 ]. de Vries’ I & SI method minimizes the sum of rank differences between inconsistently ranked individuals [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…To examine sanctuary-specific chimpanzee social group structure, we used SNA to calculate social network statistics for each individual (i.e., affinity, strength, reach, eigenvector centrality), identify significant subgroups or clusters (i.e., divisions of modularity and hierarchical clusters), and construct network diagrams (i.e., principal coordinate analyses). We also examined the dominance hierarchy of a sanctuary-living chimpanzee group using conventional methods: modified David’s scores [ 46 ], I & IS [ 47 ], Brown’s method [ 48 ], and hierarchical clusters [ 30 ]. In doing so, we aim to better advise captive management and welfare decisions for sanctuary-living chimpanzee groups with varied rearing and biomedical histories.…”
Section: Introductionmentioning
confidence: 99%
“…Such a pair bond represents the formation of a selective and a long-term social attraction between two specific adults who recognize each other and remain together after sexual activity has terminated. Monogamy usually evolves under conditions where biparental care is necessary for infant survival (Brown, 1975). …”
Section: Introductionmentioning
confidence: 99%
“…Animal behaviors are constantly evolving (Brown, 1975; Evans, 1962), and changes in existing behavioral genes (Chang et al, 2011; Fitzpatrick et al, 2007; Wheeler et al, 1991) has been suggested as an underlying mechanism. The frequent origin of new genes in the nervous system provides a novel alternative.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary functions of the brain, regardless of its level of complexity, is to control the behavior of an animal (Carew, 2000). Behaviors evolve constantly (Brown, 1975; Lowe et al, 2003), and the evolution of behavior is associated with evolution of the brain (Oro, 2004). …”
Section: Introductionmentioning
confidence: 99%